2011
DOI: 10.1017/s0265051711000039
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' use of digital technology in secondary music education: illustrations of changing classrooms

Abstract: The music industry in the 21st century uses digital technology in a wide range of applications including performance, composition and in recording and publishing. Much of this digital technology is freely available via downloads from the internet, as part of software included with computers when they are purchased and via applications that are available for some mobile phones. Such technology is transforming music and the way people approach many traditional music activities. This paper is about transformative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 25 publications
2
70
0
13
Order By: Relevance
“…A review of the literature identified that a substantial quantity of research supports the inclusion of ICT within music education in the considerations of current teaching methods (Brown, 2012;Crawford, 2009;Mark & Madura, 2010;Merrick, 1997;Southcott & Crawford, 2011;Williams, 2007;Wise et al, 2011) and professional development (Bauer, 1999;Cuban, 2001;Hixon & Buckenmeyer, 2009;Norris et al, 2003;Reese & Rimington, 2000;Sandholtz et al, 1997;Schrum, 2001;Wise et al, 2011). However, within the current body of literary knowledge, significant gaps where found to exist when considering the certainty with which ICT is implemented in music, the ICT resources used within music classrooms and how ICT resources are being utilised in music education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of the literature identified that a substantial quantity of research supports the inclusion of ICT within music education in the considerations of current teaching methods (Brown, 2012;Crawford, 2009;Mark & Madura, 2010;Merrick, 1997;Southcott & Crawford, 2011;Williams, 2007;Wise et al, 2011) and professional development (Bauer, 1999;Cuban, 2001;Hixon & Buckenmeyer, 2009;Norris et al, 2003;Reese & Rimington, 2000;Sandholtz et al, 1997;Schrum, 2001;Wise et al, 2011). However, within the current body of literary knowledge, significant gaps where found to exist when considering the certainty with which ICT is implemented in music, the ICT resources used within music classrooms and how ICT resources are being utilised in music education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Very often these technologies are considered an added value to the teaching and learning process. Arguments to backup the belief in their educational potential concern, for example, the multimodal presentation of learning content as supporting the processing of learning content ( de Jong 2010;Mayer et al 1999;Sweller, Van Merrienboer, and Paas 1998), the use of objective measurement as a way to bypass the possible ambiguity of conventional verbal feedback (Hoppe, Sadakata, and Desain 2006;Howard et al 2007), the facilitation of creating a powerful learning environment (Bransford 2000) and their appeal to young people (Burnard 2007;Prensky 2001;Upitis, Brook, and Abrami 2014;Wise, Greenwood, and Davis 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Por isso, é necessário que os docentes desenvolvam boas práticas com as crianças associadas aos dispositivos digitais (Ricoy & Valente, 2016;Wise, Greenwood & Davis, 2011) e aportem estratégias para a mudança na aprendizagem da música por meio das TIC. Neste sentido, é importante para os alunos a composição musical com o auxílio de gráficos ou aprender através de um espaço colaborativo on-line (Ruthmann, 2010;Savage, 2014).…”
Section: Revisão Da Literaturaunclassified